2015
DOI: 10.4103/0019-5413.152517
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic one-piece reshaping for symptomatic discoid medial meniscus with anomalous amalgamating into anterior cruciate ligament

Abstract: Discoid shapes of lateral menisci are relatively common finding, whereas discoid medial menisci are less common. Discoid medial meniscus with associated anomalous variants has been reported. However, symptomatic complex tear of complete type discoid medial meniscus with anomalous blending with anterior cruciate ligament is an extremely rare pathology. A 35-year-old male was admitted to our hospital with left knee pain and loss of terminal extension for 2 years. On physical examination, the patient presented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…No consensus has been reached on the treatment of an anomalous insertion of the anterior horn of the medial meniscus into the ACL, and it is important to establish whether the patient's symptoms are being caused by the anomalous insertion. 21 Santi and Richardson 22 described a patient whose symptoms were fully relieved by resection of the anomalous insertion. Shea et al 13 reported a case of anomalous insertion of the medial meniscus with subluxation of the patella.…”
Section: Discussionmentioning
confidence: 99%
“…No consensus has been reached on the treatment of an anomalous insertion of the anterior horn of the medial meniscus into the ACL, and it is important to establish whether the patient's symptoms are being caused by the anomalous insertion. 21 Santi and Richardson 22 described a patient whose symptoms were fully relieved by resection of the anomalous insertion. Shea et al 13 reported a case of anomalous insertion of the medial meniscus with subluxation of the patella.…”
Section: Discussionmentioning
confidence: 99%